Monitoramento por dgps e análise dos processos erosivos da linha de costa na praia de Pirangi do Norte - Parnamirim / RN - Nascimento, Kleiton Cassemiro do (2009)
Through out the course of a steady increase in search and recovery of space in the coastal zone, there is also an expanding concern about the erosion processes of this area. The main problem in coastal areas is that urbanization occurs in a disorderly fashion and unsustainable, further aggravating the problems of coastal dynamics. The study area of this work is located on the southern coast of Pirangi do Norte beach to about 20km south of Natal, capital of Rio Grande do Norte in the Parnamirim City. This area has the length of approximately 1km, divided into three sections (Western, Central and Eastern) with a morphology consisting of a tableland at the top, sea cliffs in the West and Central parts and sand dunes in the Eastern section, both vegetated, and a coastal plain on the inferior part associated with the presence of beach rocks. This study aimed to analyze the erosion processes operating in the excerpt of Pirangi do Norte beach and assess the feasibility of their monitoring making use of DGPS (Global Positioning System Differential mode). During the work it was carried out a physical description of the area through photo-interpretation and site survey after measurement of the shoreline in the period between November 2004 and November 2009 and beach profiles between August 2005 and July 2006. The analysis of the results of the annual surveys showed the occurrence of variations of the shoreline along the stretch traveled. Sites are identified in advancement coast from the sea and it was verified in loco the presence of erosion with deposition of materials on the lower part of the coastal bluff, the former position of the shoreline, showing a false notion of advancing it. This leads to the conclusion that the data collected in a survey of the shoreline should always be accompanied by photographic records of the local area and with the highest rate of erosion, thus avoiding the mistake of treating the deposit materials as evidence of progress coast. At the end of the study, after a review of various works to mitigate the erosion in the coastal zone, it is recommended to the area of study the adoption of an artificial feeding of the beach, aiming the minimization of the erosive effects of the tides. Moreover, it is suggested that even the continuity of monitoring, maintenance of existing vegetation and control of the occupation on the edge of sea cliffs